2019
DOI: 10.1101/gr.245159.118
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis of 3′ UTR sequence elements and proteins regulating mRNA stability during maternal-to-zygotic transition in zebrafish

Abstract: Posttranscriptional regulation plays a crucial role in shaping gene expression. During the maternal-to-zygotic transition (MZT), thousands of maternal transcripts are regulated. However, how different cis-elements and trans-factors are integrated to determine mRNA stability remains poorly understood. Here, we show that most transcripts are under combinatorial regulation by multiple decay pathways during zebrafish MZT. By using a massively parallel reporter assay, we identified cis-regulatory sequences in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 89 publications
(131 reference statements)
4
57
0
Order By: Relevance
“…RNA-seq and data processing of high-throughput sequencing. The total RNA of unfertilized eggs and embryos at different developmental stages of wild type and mutant zebrafish were isolated with TRIzol reagent, and mRNA was purified from total RNA as described previously 41 . Purified mRNAs and RIP-RNAs were fragmented and RNA library was constructed using NEBNext® Ultra II Directional RNA Library Prep Kit for Illumina (NEB, E7760) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq and data processing of high-throughput sequencing. The total RNA of unfertilized eggs and embryos at different developmental stages of wild type and mutant zebrafish were isolated with TRIzol reagent, and mRNA was purified from total RNA as described previously 41 . Purified mRNAs and RIP-RNAs were fragmented and RNA library was constructed using NEBNext® Ultra II Directional RNA Library Prep Kit for Illumina (NEB, E7760) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The 3 UTRs of zebrafish mRNAs are structurally dynamic and changes in their structure can regulate the stability of mRNAs during MZT by modulating miRNA activity [39]. In addition, the 3 UTRs of zebrafish mRNAs are enriched in cis-acting regulatory elements that control mRNA decay during MZT and have been characterized in detail using a high-throughput RNA-element selection assay (RESA), which enables to identify sequences regulating RNA stability with near nucleotide resolution [75]. An in vivo study of heat-regulated RNA structuromes in rice showed that mRNA unfolding is correlated with RNA half-life and supports the importance of both UTRs for mRNA stability in plants [52].…”
Section: Rna Structure In Relation To Rna Stability and Degradationmentioning
confidence: 99%
“…Similarly, an SNP site in the 3′ UTR of the human BMP2 gene is associated with the formation of human subcutaneous fat [22]. It is widely believed that 3′ UTR regulatory regions are involved in post-transcriptional regulation and play an important regulatory role in mRNA stability, gene transcription efficiency, and expression localization [23][24][25]. It remains to be seen whether the three sites we found in the 3′ UTR of the sheep BMP2 gene contribute to post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 79%